Neuroprotective Efficacy of Prophylactic Antiepileptic Therapies in Busulfan Conditioning Regimen - Cokyaman, Turgay; Elli, Murat; Aydin, Ömer F.; Albayrak, Canan; Albayrak, Davut; Özyürek, Emel (Journal of Pediatric Neurology, 2020)
Busulfan (BU) is commonly used in the anticancer treatment and bone marrow/hematopoietic stem cell transplantation (BM/HSCT) conditioning regimen. This study aimed to evaluate the neuroprotective efficacy of antiepileptic therapies in the BU conditioning regimen. Patients who underwent BM/HSCT between January 1, 2009, and January 1, 2014, were evaluated retrospectively. Diagnosis, demographic characteristics, neurological side effects, electroencephalography (EEG) abnormalities, and antiepileptic drugs were determined. Levetiracetam was given to 49% and phenytoin to 23% of patients as antiepileptic prophylaxis. After BU treatment, seizures developed in three patients, posterior reversible leukoencephalopathy in two patients, and peripheral neuropathy in two patients. Forty-five patients who underwent EEG before and after BU treatment were identified. The effects of antiepileptic prophylaxis over the electroencephalographic abnormalities after the BU conditioning regimen were found to be not different (p = 0.491). Neurological side effects and electroencephalographic abnormalities following BU conditioning regimen under antiepileptic prophylaxis are comparable.
Keywords: antiepileptic prophylaxis; busulfan; levetiracetam